The gut–brain–circadian axis in anxiety and depression: a critical review - Bautista, Jhommara; Hidalgo-Tinoco, Camila; Di Capua Delgado, Miranda; Viteri-Recalde, Juliana; Guerra-Guerrero, Antonio; López-Cortés, Andrés (Frontiers in Psychiatry, 2025)
Anxiety and depressive disorders rank among the most prevalent psychiatric conditions worldwide, yet remission rates remain unsatisfactory despite advances in pharmacological and psychotherapeutic interventions. The gut–brain axis has emerged as a transformative framework for understanding these disorders, emphasizing bidirectional communication between the central nervous system, the enteric nervous system, the endocrine and immune systems, and the gut microbiota. Preclinical studies demonstrate that germ-free or dysbiotic states exaggerate hypothalamic–pituitary–adrenal (HPA) reactivity, remodel synaptic plasticity, and induce anxiety- and depression-like behaviors, while fecal microbiota transplantation confirms the causal influence of microbial communities. Mechanistically, neural (e.g., vagal), endocrine (e.g., cortisol), immune (e.g., cytokine), and metabolic (e.g., short-chain fatty acids, tryptophan metabolites, bile acids) pathways converge to regulate mood and stress resilience. An underappreciated yet critical dimension of this model is circadian rhythmicity. Both host endocrine cycles and microbial communities exhibit diurnal oscillations that synchronize metabolism, immune activity, and neural signaling. Disruption of these rhythms, through factors such as sleep disturbance, irregular feeding, or shift work, alters microbial diversity, dampens metabolite oscillations, destabilizes HPA regulation, and enhances neuroinflammation, thereby amplifying vulnerability to psychiatric disorders. Collectively, evidence supports a model in which anxiety and depression are systemic conditions arising from integrated neural, immune, endocrine, metabolic, and circadian dysregulation, rather than isolated brain-based pathologies. This reconceptualization positions microbial taxa and metabolites as candidate biomarkers and therapeutic targets. Precision interventions, ranging from diet and psychobiotics to fecal microbiota transplantation, chrononutrition, and immune-modulatory strategies, offer promising avenues for personalized psychiatry.